Leptospira borgpetersenii serovar hardjo type hardjobovis in bovine embryos fertilized in vitro. - Bielanski, A B (1998)
The association of Leptospira borgpetersenii serovar hardjo type hardjobovis with bovine embryos produced by in vitro fertilization was examined by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Morula stage embryos with an intact zona pellucida (ZP) were exposed to this spirochete for 24 h in culture medium, washed by the standard washing procedure as recommended by the International Embryo Transfer Society, and then examined. SEM showed typical helicoid leptospires on the surface and in the pores of the ZP. TEM showed cross and longitudinal sections of leptospires in the matrix and channels of the ZP, in the perivitelline and intercellular spaces, on the vitellus and in the embryonic cells. Some of the embryos that were penetrated showed damage to the membranes and the cytoplasm. The ineffectiveness of the washing procedure, for the removal of hardjobovis from exposed embryos may be of importance to the industry.